PENGARUH PERTUMBUHAN EKONOMI DAN PENYERAPAN ANGKATAN KERJA TERHADAP KEMISKINAN DENGAN PENDAPATAN PERKAPITA SEBAGAI VARIABEL PEMODERASI - Robiansyah . (KINERJA, 2015)
This study aimed to describe the conditions of employment in Bulungan area taking into account economic growth, employment, and income per capita as the antecedents and, consequently poverty. Then conducted empirical testing to see moderating effect of per capita income. The method used in this research in the form of quantitative descriptive. The results showed no effect of economic growth on povserty levels. However, the absorption of the workforce factor effect on poverty reduction. Moderating effects of per capita income only affects the variable absorption of the labor force, whereas moderating effects on economic growth have no effect.keywords: Economic Growth, Absorption Labor Force, Poverty Reduction